Development of biotechnology for cultivating Potentilla L. plant material with antivirus and antibacterial activity. Issue 1 (December 2020) - Tikhomirova, L I; Zaripova, AA
Abstract: The reported paper presents a biotechnology developed to produce phytomass of Potentilla L. species (P. alba, P. fragarioides, P. fruticosa, P. chrisantha, P. longifolia). Regenerative Potentilla plants are good at extracting bio-friendly elements (Pb, Cu, and Zn) from the Murashige and Skoog growth medium and accumulating them. Water extracts of plant material P. alba, P. fragarioides, P. fruticosa, P. chrisantha, P. longifolia have shown a good biological activity against herpes simplex virus type II. Extracts of bio-technologically produced Potentilla alba plants have demonstrated an antibacterial activity against E. coli, K. pneumoniae, S. typhimurium, St. aureus taken in a minimal dose of 37.5 μg/ml.